(untitled) (Praxis Educativa, 2012)
The Pos-grade Title in Socio-Institutional Analysis and Animation, designed and coordinated by the Lic. Lidia Fernandez, proposed the formation of professors of the Institutes of Teaching for being “extensionistas”. The curricular design put the axis in the work in intensive residential laboratories. The “forced coexistence”, the accumulation of intensive working hours throughout the week, as well as the “intensity” of the time lived as a result of the high degree of personal involvement required by the task, allowed the appearance and the analysis of peculiar phenomena that produced formative effects of high interest. In the first part, I am going to focus in the formative effects that these phenomena have had in the participants. In the second part, I am going to center the analysis in the impact of these same phenomena in the dynamics of the coordinating equipment and in the conditions required for the exercise of this task.